Antimicrobial sensitivity of Escherichia coli and Enterococcus species isolated from table eggs, and backyard poultry farmers’ knowledge and attitudes on responsible antimicrobial use in Balfour, Dipaleseng Municipality of Mpumalanga Province, South Africa - Keddy, Karen H. (University of Pretoria, 2025)
Mini Dissertation (MSc (Global One Health))--University of Pretoria, 2024.